Prototyping and Characterization of Gripper Technologies for Stiff Fabric Material - Vivek Kumar; Mihail Fontul; Carlos Neves; Paulo Jorge Coelho (IEEE Access)
This study explores robotic gripper technologies to automate the handling of rigid, porous, and fibrous polymer fabric pads, used in automotive acoustic applications. Currently handled manually, these materials present challenges due to their rough texture and structural rigidity. Various grippers were designed and tested, including vacuum suction, high-airflow systems, Bernoulli ejectors, needle penetration, Velcro, adhesives, cryogenics, mechanical friction, and electro-adhesion. The grip strength in the normal and shear directions was evaluated using a custom measurement system and an industrial robot to simulate detachment. Key metrics included maximum grip force and material integrity after testing. The comparative results highlight the trade-offs between grip security and potential material damage across different technologies. This comprehensive evaluation provides engineers and system designers valuable insights for selecting and optimizing gripper systems tailored to non-woven polymer fabric materials. The findings contribute to advancing automated handling solutions, promoting efficiency, consistency, and reduced manual labor in manufacturing environments.